The ultra vires doctrine as applied to companies: a comparative study / K. Ganesan Kasinathan - K. Ganesan, Kasinathan (2000)
A comparative dissertation presented on the history and development of the doctrine of Ultra Vires as applied to companies, beginning with the origins of the doctrine and its development in England, up until the Companies Act 1989 (UK), covering reforms of the Ultra Vires doctrine in English law; its application and position in Malaysia, and a consideration and development of Ultra Vires in Australia particularly in respect of the Corporation Law.